Like a Wave in Its Variable Shape, Breadth, and Depth: A Qualitative Interview Study of Experiences of Daytime Sleepiness in People with Parkinson’s Disease - Arja Höglund; Peter Hagell; Ulrika Östlund; Sten Fredrikson; Christina Sandlund (Parkinson's Disease)
Introduction. Daytime sleepiness is a common nonmotor symptom in Parkinson’s disease (PD) which is associated with decreased quality of life and perceived health. However, experiences of daytime sleepiness in people with PD have not been explored. The aim of this qualitative study was to explore experiences of daytime sleepiness in people with PD. Materials and Methods. Five women and seven men (42–82 years) with PD for 1.5 to 21 years and excessive daytime sleepiness (i.e., a score of >10 on the Epworth Sleepiness Scale) participated in the study. Data were collected through individual, semistructured, face-to-face interviews and analyzed with qualitative content analysis. Results Three themes of the experience of daytime sleepiness were revealed: (1) not an isolated phenomenon, (2) something to struggle against or accept, and (3) something beyond sleepiness. Conclusion. Daytime sleepiness is a complex nonmotor symptom in PD which manifests itself in several ways. Some experiences are similar, for instance, the attribution of daytime sleepiness to PD and its medical treatment. Differences depend on how sleepiness manifests itself, affects the person, and impacts daily life, as well as whether it causes feelings of embarrassment. Some participants needed to struggle against daytime sleepiness most of the time, and others had found a way to handle it, for example, with physical activity. However, sleepiness may also be used to benefit the person, for example, if they allow themselves to take a power nap to regain energy. The health care professionals can easily underestimate or misinterpret the prevalence and burden of daytime sleepiness because people with PD may describe daytime sleepiness as tiredness, drowsiness, or feeling exhausted, not as sleepiness.